LISTENING TEXTS AND LISTENING STRATEGIES - Scientifik advisor: Teshaboyeva Nafisa Zubaydulla qizi Author: Toʻraqulova Maxsuma Neʼmat qizi Jizzax branch of National University of Uzbekistan named after Mirzo Ulugʻbek The faculty psychology The Department Philology; teaching languages: English (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2024)
Listening is a fundamental skill in language acquisition, serving as a cornerstone for effective communication and comprehension. This study explores the significance of listening texts and strategies in enhancing learners’ ability to process and interpret spoken language. Listening texts, which include dialogues, monologues, and multimedia content, provide authentic contexts that expose learners to various accents, speech rates, and language structures. Listening strategies, such as predicting content, inferring meaning, and using contextual clues, help learners overcome comprehension barriers and improve their overall listening proficiency. Key words Listening comprehension, Authentic listening texts, Listening strategies, Language learning process,Spoken language input,Active listening skills, Language proficiency development, Communication competence, Strategy-based learning, Language pedagogy